In-between Spaces: Unconventional Yet Essential Considerations for Defence and Security - Gitanjali Adlakha-Hutcheon (The Journal of Intelligence, Conflict and Warfare)
Dr. Adlakha-Hutcheon discussed dualities between obvious pairs such as defence and security; science and technology; and the physical and virtual worlds and questioned at what point does one become the other? Whether these were truly distinct or continuums with messy middles.  Furthermore, it is necessary to understand the middle/liminal spaces between pairs in order to more effectively identify and address security threats. This is apparent when one takes the example of established/emerged and emerging technologies (AI and emergence of generative AI like Chat GPT).  Technologies have different impact and implications based on the context of their use, for instance the extent of positive or negative disruption that ensues upon their use. Thus, to address complex problems, it is necessary to look for disruptors in “in-between” spaces.